Features and Usefulness of Alipay - Mushtaq, Mubshira; Ashfaq, Kalsoom; Almas, Humeria; Qadeer, Iqra (Advances in Social Sciences Research Journal, 2019)
In virtual market and advanced technology, mobile payment application Alipay emerged prominently having strong competitive edge over rivalry. This application was initiated by Alibaba and nowadays leading with market shares. Its quite common and useful in everyday life especially in china where payments and receipts are surrounds QR (Quick Response) codes. This application just adds more convenience to routine life to quite big transactions. People of all categories and occupations are using Alipay in china. Other than china this application is also diversifying its roots internationally. Alipay is very famous & popular electronic application in china. Alipay is safe, simple & convenient application. It is now in trend. Alipay technology is at maturity level in china. It is very useful in daily life activities like online shopping, in restaurants, booking of tickets, for business purposes, for home delivery of